Efficacy of Lidocaine and Ketamine Combination on Reduction of Pain Intensity, Improvement of Functional State and Central Desensitization of Chronic Low Back Pain - Henry Sugiharto; Hasnawi Haddani; Yuki Fitria; Rizal Zainal (HM Publisher, 2020)
Abstract Background: Chronic low back pain (LBP) prevalence is approximately 20% of world population. Central and peripheral sensitization are considered as the main mechanism of pain chronification. This study hypothesize that lidocaine and ketamine combination reduces pain intensity, improves functional state and central desensitization of chronic low back pain. It is by modulating central sensitization in sub-anesthetic dose, prolonging inactivation of Na-channel, blocking NMDA-receptor and preventing secondary hyperalgesia. Aim of study: To evaluate the efficacy of lidocaine and ketamine combination on the intensity of pain, functional state and central desensitization of chronic low back pain. Methods:. This double blind randomized control trial study was carried out in Mohammad Hoesin General Hospital, Palembang, Indonesia from May 2018 to January 2019. A total of 20 patients with low back pain that last for more than 3 months, aged >18 years old, of either sex who were willing to be enrolled in this study, were randomly allocated into one of the two groups of 10 each. The treatment group (n=10) received standardized therapy (analgesic and physiotherapy) + intravenous ketamine 0.5 mg/kg + lidocaine 2 mg/kg and the control group (n=10) received standardized therapy + 100 ml Nacl 0.9%. Pain intensity, functional state, and central desensitization were measured before the treatment, day 7 after treatment, and a month after treatment using Numeric Pain Rating Scale (NPRS), Functional Pain Scale (FPS), and Central Sensitization Inventory (CSI). Results: The administration of ketamine 0.5 mg/kg + lidocaine 2 mg/kg resulted in NPRS and CSI changes was effective since the 7th day post intervention (p-value=0.021 and p-value=0.001) while on FPS changes, it was effective since the 30th day post intervention (p-value=0.000) Conclusion: From the result, it could be concluded that the administration of ketamine and lidocaine is effective on decreasing pain intensity and central desensitization in chronic LBP.